The Pantawid Pamilyang Pilipino Program: Towards Women’s Empowerment or Further Entrapment? (Voices of Beneficiaries in Legazpi City) - Laguilles, Rowena Ayque (Philippine Journal of Social Development; Vol 4 (2012): Philippine Journal of Social Development)
-